Design of Alporas aluminum alloy foam cored hybrid sandwich plates using Kriging optimization - Lim, Yee Wei (2014)
Sandwich structures are shown to have better blast resistance when compared to the solid metallic plate for the same weight. Hybrid Sandwich Panel (HSP) further increases the blast resistance with addition of hyper-elastic material in between the face sheet and core. In this paper, the studied HSPs are composed of five layers, where the front and back face sheets are made of Rolled Homogeneous Armor (RHA) steel, and two interlayers of polyurethane (PU) and aluminum alloy foam (Alporas™) core. Finite element analysis (FEA) software (Abaqus®) is used to simulate deflection and energy absorption of a circular clamped HSP under a spherical blast loading from a fixed distance. Twenty-eight FE models with different design configuration are sampled using modified Grid Sampling method. Based on the FE simulated samples, a surrogate model is developed using Kriging for the fast computation of the HSP performance in the design optimization. The HSP is optimized to achieve two conflicting objectives, light weight and high energy absorption, with an overall panel thickness limit of 100 mm.